The effect of e-service quality on e-loyalty through e-satisfaction e-commerce users in West Sumatra - Alexander; Awisal Fasyni (Operations Management and Information System Studies, 2023)
Both the number of web clients in Indonesia and the development of web-based businesses have happened rapidly in Indonesia. The number of new web businesses emerging and making will simplify it for customers to make relationships of purchasing a comparable thing between different online businesses. In order to maintain customer loyalty, e-commerce may face new competition as a result of this situation. This study focuses on Tokopedia users in West Sumatra who use e-commerce. It uses e-satisfaction as a mediating variable to examine the connection between e-loyalty and e-service quality. This kind of research is called illustrative investigation, and it uses speculation testing to figure out how different research factors are related to one another. The non-likelihood testing and the purposeful inspection strategy are the methods of examination that are used. The study included 170 individuals who were all Tokopedia customers, had purchased more than twice, and were at least 17 years old. The product SmartPLS 4.0 was utilized to help with the halfway least square (PLS) examination of the information. According to the findings of this study, e-service quality has a positive and significant effect on e-loyalty, e-satisfaction has a positive and significant effect on e-loyalty, and e-loyalty is mediated by e-satisfaction by e-service quality.